Recurrent Swarms of Planktonic Shrimp Luciferidae De Haan, 1849 (Order: Decapoda) in the Neritic Waters of Tamil Nadu, Southeast Coast of India - R. S. Sathishkumar; B. Charan Kumar; C. Muthukumar; N. Logesh; Sanitha K. Sivadas; K. Ramu; M. V. Ramana Murthy (Marine Ecology, 2024)
Luciferidae (Decapoda) are an important component of mesozooplankton in pelagic food webs. This study investigated the spatiotemporal distribution and frequency of Luciferidae swarms along the Tamil Nadu coast, as observed during coastal monitoring cruises conducted between 2019 and 2022. Data were collected on various hydrobiological factors, including surface water temperature, salinity, chlorophyll a , zooplankton biomass, and the abundance of other mesozooplankton (such as copepods, cladocerans, and others) across eight locations in the coastal waters of Tamil Nadu, India. Salinity values were generally low ( Belzebub hanseni Nobili, 1905, as the only organism responsible for swarm formation, with its occurrence peaking in January 2022. During this period, B. hanseni reached a maximum abundance of 3294 ind. m −3 for adults and 4056 ind. m −3 for larvae, together contributing approximately 27% of the total zooplankton abundance. Swarms of B. hanseni were observed a total of seven times over the course of the study, correlating with periods of low sea surface temperature and high food availability. Pearson's correlation analysis revealed a significant relationship between the abundance of copepods and B. hanseni ( r = 0.84; p B. hanseni in the nearshore waters of the Tamil Nadu coast is largely driven by food availability and optimal environmental conditions, including water temperature and monsoonal influences. The findings also suggest that geographical features, such as mangrove habitats, may contribute to the occurrence of B. hanseni swarms in this region.

Study on groundwater pollution and its human impact analysis using geospatial techniques in semi-urban of south India - Vivek S; Umamaheswari R; Subashree P; Rajakumar S; Mukesh P; Priya V; Sampathkumar V; Logesh N; Ganesh Prabhu G (Environmental Research, 2024)